1986
DOI: 10.1001/jama.1986.03370160075030
|View full text |Cite
|
Sign up to set email alerts
|

Impact of a Rural High Blood Pressure Control Program on Hypertension Control and Cardiovascular Disease Mortality

Abstract: Kentucky is a predominantly rural state with relatively high death rates from hypertension and cardiovascular disease. We report the results of a community-based high blood pressure control educational program undertaken in two rural counties of southeastern Kentucky. In the intervention counties, systolic and diastolic blood pressures of both men and women decreased despite the five-year increase in age; moreover, hypertension was better controlled after the program, and substantial decreases in deaths due to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

1991
1991
2009
2009

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 9 publications
0
21
0
Order By: Relevance
“…Three trials compared the effects of interventions on physical activity, 20-22 one on smoking 23 and five on multiple risk factors. [24][25][26][27][28] One trial was conducted in Belgium 20 and the remainder in the USA. [21][22][23][24][25][26][27][28] With one exception 26 all trials reported on women only.…”
Section: Description Of Studiesmentioning
confidence: 99%
See 3 more Smart Citations
“…Three trials compared the effects of interventions on physical activity, 20-22 one on smoking 23 and five on multiple risk factors. [24][25][26][27][28] One trial was conducted in Belgium 20 and the remainder in the USA. [21][22][23][24][25][26][27][28] With one exception 26 all trials reported on women only.…”
Section: Description Of Studiesmentioning
confidence: 99%
“…Participants were recruited from the workplace, 24 a women's organisation, 20 through articles or advertisements in local newspapers, flyers and announcements at meetings, 22,25,26 community clinics and private practices 21,27 and through community networks such as churches and businesses in the area. 26 With one exception 26 all the remaining studies were of women only.…”
Section: Participantsmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, Sutterer, Carey, Silver, and Nash (1989) found that, while community screening did increase knowledge of hypertension, it did not necessarily lead to risk modification. On the other hand, Kotchen et al (1986) demonstrated that the prevalence of hypertension in a rural community could be reduced through a hypertension screening program. As discovered in worksite screening programs, the success of community screening is largely dependent on whether the participants seek appropriate follow-up care.…”
mentioning
confidence: 99%